Hubungan Pendidikan dan Pelatihan dengan Pelaksanaan Sistem Pemberian Pelayanan Keperawatan Profesional oleh Perawat Pelaksana di Ruang Rawat Inap RSUD Raden Mattaher Jambi - Indah Mawarti; Fatma Sri Wahyuni; Wawan Wahyudi (Jurnal Ilmiah Universitas Batanghari Jambi, 2020)
Professional nursing service delivery system (SP2KP) is a component of the application of professional values in nursing practice, management and nursing care provision in hospital ward units and self-professional development. The purpose of this study was to determine the relationship between education and training with the implementation of SP2KP by implementing nurses in the inpatient room of Raden Mattaher Jambi Hospital. The type of research carried out in this study is a quantitative study using an analytic research design with cross sectional approach (n = 132 nurses). The test used in this study is the Chy-Square test. Data is collected by using a questionnaire that has been tested for validity and reliability. The results of the study of the relationship between education and training with the implementation of a professional nursing service delivery system by implementing nurses in the Inpatient Room of Raden Mattaher Jambi Hospital. Education that has a significant relationship with the implementation of SP2KP (p value = 0.010). Researcher's suggestion to implementing nurses to improve education will affect the skills and knowledge of implementing nurses in the implementation of SP2KP in the inpatient room of Raden Mattaher Jambi Hospital.